The Relationship Between Academic Stress And Mental Health Of Medan Area University Students - Yulina , Eva; Yunita, Yunita; Kesuma Dewi, Ira; Gama Samudera Lubis, Doli Maulana (Green Publisher Indonesia, 2025)
This study examines the relationship between academic stress and mental health among students at the University of Medan Area (UMA). Academic stress caused by demanding assignments, exams, and high expectations can affect students' emotional and social well-being. This study used a quantitative approach with a correlational design and involved 200 UMA students. Data were collected using a questionnaire that measured academic stress levels and mental health conditions, including anxiety, depression, and burnout. The results showed that 64.5% of students experienced moderate to high levels of academic stress, which was comparable to mental health disorders, specifically anxiety (58.3%) and burnout (53.2%). The Pearson correlation test yielded a value of r = 0.748 (p = 0.000), indicating a significant positive relationship between academic stress and mental health. The reliability test showed Cronbach's Alpha values for the academic stress and mental health scales of 0.902 and 0.921, respectively, indicating excellent reliability. Factors contributing to academic stress include assignment load, tight deadlines, and high academic expectations. This study concluded that academic stress significantly influences students' mental health. Therefore, universities need to provide support such as counseling services, stress management training, and increased social support to help students cope with stress and improve their psychological well-being.